Internationalization of MBA Program in Asia-Pacific: Looking Beyond Business Study Missions - TAN, Teck Meng (Institutional Knowledge at Singapore Management University, 1997)
With the global village becoming a reality, efforts at the internationalization of business education have ceased to be merely fashionable. The internationalization of business education has become an increasing relevant and important goal for business schools. Most of the efforts have been focused at the internationalization of MBA programs as this is the level of business education targeted at the training of middle management personnel, for whom the creation of a global mindset and the exposure to the international realm of business would have the most immediate effect. With the Asia-Pacific becoming a major arena of international trade and business in what has been called the Pacific century, the internationalization of MBA programs in Asia is of great interest as most of the efforts at internationalization of MBA programs have taken place in developed countries, with much of the literature being about the North America and European experience. Little is known about the MBA programs offered in Asia and their internationalization. This paper provides some insights on the internationalization efforts at the Nanyang Business School (NBS), Singapore. The experience at the NBS is unique because its efforts at internationalization have coincided with government policy initiatives in encouraging Singapore businesses to extend their operations into countries of the region. The paper provides some lessons from the experiences at regionalizing the MBA programs in China, India and the transitional economies of Vietnam, Myanmar and Cambodia. Apart from the admission of international participants to its programs and the changes to its Business Study Missions, new initiatives have been introduced in the form of the MBA in International Business. The paper also explores other future initiatives for the internationalization of MBA programs in Asia-Pacific.